If f ( x ) = 4 x 2 − 2 x + 3 f ( x ) = 4 x 2 – 2 x + 3 , find f ‘ ( − 5 ) f ′ ( – 5 ) . Use this to find the equation of the tangent line to the parabola y = 4 x 2 − 2 x + 3 y = 4 x 2 – 2

Need your ASSIGNMENT done? Use our paper writing service to score better and meet your deadlines.


Order a Similar Paper Order a Different Paper

If

f

(

x

)

=

4

x

2

2

x

+

3

f

(

x

)

=

4

x

2

2

x

+

3

, find

f

(

5

)

f

(

5

)

.

Use this to find the equation of the tangent line to the parabola

y

=

4

x

2

2

x

+

3

y

=

4

x

2

2

x

+

3

at the point

(

5

,

113

)

(

5

,

113

)

. The equation of this tangent line can be written in the form

y

=

m

x

+

b

y

=

m

x

+

b

where

m

m

is:

and where

b

b

is:

"Is this question part of your assignment? We can help"

ORDER NOW
Writerbay.net

Do you need help with this or a different assignment? We offer CONFIDENTIAL, ORIGINAL (Turnitin/LopesWrite/SafeAssign checks), and PRIVATE services using latest (within 5 years) peer-reviewed articles. Kindly click on ORDER NOW to receive an A++ paper from our masters- and PhD writers.

Get a 15% discount on your order using the following coupon code SAVE15


Order a Similar Paper Order a Different Paper